2014 6th International Conference on Games and Virtual Worlds for Serious Applications (VS-GAMES) 2014
DOI: 10.1109/vs-games.2014.7012029
|View full text |Cite
|
Sign up to set email alerts
|

Aliens versus Humans: Do Avatars Make a Difference in How We Play the Game?

Abstract: an immersive first-person 3D computer game was designed and developed to investigate if the visual characteristics of a player's avatar influences their behavior. Two types of gender-matched biped avatar were used: Normal looking Humanoids and tougher looking Aliens. In the game, players had to block incoming projectiles fired from two canons with their hands. The number of times the players were hit as well as a measure of how hard they hit the projectiles was recorded. Results show differences in these measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…The results suggest that it may be important for many virtual reality applications that aim to convey and transfer spatial information from the virtual world to the real world to provide a personalized avatar in terms of size. Avatars are used in various applications and research fields such as health care (Stevens et al, 2006;Combs et al, 2015), education (Hayes et al, 2013), tele-communication (Slater and Steed, 2002;Garau et al, 2003;Bailenson et al, 2006;Biocca, 2014), immersive games (Christou and Michael, 2014), virtual clothes try on and animation of realistic clothing (Magnenat-Thalmann et al, 2011;Guan et al, 2012;Pons-Moll et al, 2017), design processes (Sherman and Craig, 2002), and ergonomics (Badler, 1997;Honglun et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The results suggest that it may be important for many virtual reality applications that aim to convey and transfer spatial information from the virtual world to the real world to provide a personalized avatar in terms of size. Avatars are used in various applications and research fields such as health care (Stevens et al, 2006;Combs et al, 2015), education (Hayes et al, 2013), tele-communication (Slater and Steed, 2002;Garau et al, 2003;Bailenson et al, 2006;Biocca, 2014), immersive games (Christou and Michael, 2014), virtual clothes try on and animation of realistic clothing (Magnenat-Thalmann et al, 2011;Guan et al, 2012;Pons-Moll et al, 2017), design processes (Sherman and Craig, 2002), and ergonomics (Badler, 1997;Honglun et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We explore the approach in two target-selection tasks; earlier work on avatars that differ from users' real bodies have also used target selection [6,37]. In a first study, we evaluate our approach by adapting avatar forearm length for a 3D tapping task.…”
Section: Session 9b: Interpreting and Adapting Hand Inputmentioning
confidence: 99%
“…For instance, embodying a taller avatar increases self-confidence during a negotiation [39]. Christou and Michael [6] focused on the effect of appearance and body ownership on performance. They used realistic humanoid avatars with two different textures.…”
Section: Avatars That Differ From Users' Bodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants in the conditions with multiple gaming sessions were asked to log in to their account to start the next session, where they could continue at the same level they had reached when they stopped playing at the end of a previous session. Having created an account, participants were asked to build their own avatar in order to increase their engagement in the game (Birk, Atkins, Bowey, & Mandryk, 2016;Christou & Michael, 2014;Lindgren, 2013). We decided that this would be beneficial even though it has been shown that a participant's input on game aesthetics has only a limited influence on its effectiveness (DeSmet et al, 2016).…”
Section: Methodsmentioning
confidence: 99%